Serviços de informação tecnológica: fatores condicionantes da transferência de tecnologia para pequenas e médias indústrias químicas - Torres, Ricardo de Gil (2004)
Micro, small and medium size enterprises have a significant participation in the gross national product and the number of jobs of most countries. All around the world, several programs has been developed to support and increase the competitiveness of these enterprises. Among them, technological information services were created to facilitate the access of small and medium enterprises to the technology producers, namely universities and research Institutes. In Brazil a wide network of technological information centers was created during the 1980’s and 1990’s which, throughout the years, was dismantled due to lack of demand from small enterprises. This study was conducted with the purpose of identifying the reasons behind this lack of demand, since the need of information by small companies is far from being fulfilled. The sources of information, namely information services, and the receivers of information, namely small companies, were both analyzed. A gap was observed between information services and their target public which gradually repelled the latter. This phenomenon does not affect information services only in Brazil. All over the world, these services have been restructuring themselves in order to better meet their target public’s needs and to become financially selfsufficient. This study gives suggestions as to how Brazilian technological information services should act during transition stage.